Risk of Malignancy Index is not accurate as a Triage Tool for Ovarian Cancer - Gregorius Tanamas; Jasmine Iskandar; Tofan W Utami; Tricia D Anggraeni; Kartiwa H Nuryanto (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To evaluate Risk of Malignancy Index (RMI) as a triage tool for ovarian cancer in Dr. Cipto Mangunkusumo Hospital. Method: This is a retrospective study conducted from January 2008-December 2012 in patients diagnosed with ovarian mass. Patients admitted for surgery due to ovarian masses were included to this study. RMI 3 score was calculated based on ultrasonography examination in Dr. Cipto Mangunkusumo Hospital, CA-125 test and menopausal status. Patients without final pathological report and incomplete data were excluded from study. Data were analysed using SPSS 20 to evaluate RMI result and final pathlogical report in benign and malignant case. Result: From 882 patients identified with ovarian masses from cancer registry, only 99 patients aged 17-70 y.o were included in this study. Most of the patients were nully-parity (28.3%), non-menopausal women (60.6%), normal body mass index (40.4%), and with stage IIIC ovarian cancer (33.3%). Ultrasonography examination showed that most of patients had solid mass and ascites (19.2%). Meanwhile, CA-125 showed that patients with <35 U/ml were 10.1% and â‰¥ 35 U/ml were 89.9%. Patients with RMI scores <200 (benign cases) were 19 cases (19.2%) and â‰¥ 200 (malignant cases) were 80 cases (80.8%). Meanwhile, patients with benign final pathological report were 23 cases (23.2%) and malignant cases were 76 cases (76.8%). There was no statistical difference in RMI between benign and malignant cases based on final pathological report. Conclusion: Our study showed that RMI was not accurate as triage tool for ovarian cancer in our hospital. Further investigation and more patients are needed to confirm this study. Keywords: CA-125, menopausal status, ovarian cancer, risk of malignancy index (RMI), ultrasonography.